Procrastination and Aggression for Mental Disorders in Young People - Zvereva M. V. (Психологическая наука и образование, 2015)
The article presents analyze the phenomenon of procrastination and indirect manifestations of aggression in young people in normal health and mental disorders. Procrastination - a frequent phenomenon among young people, for this category the term “academic procrastination”; the high level of the various manifestations of aggression can also accompany adolescents in health and disease. The purpose of research is analysis of the relationship of procrastination and manifestations of aggression in health and mental disorders in adolescence. A complex of methods of psychological diagnosis, which included: questionnaire “Procrastination Assessment Scale for Students” (PASS, Solomon & Rothblum, 1984) Rosenzweig Frustration Test, Wagners Hand Test. We studied two samples of subjects 18-25 years: a control group of healthy young people (boys and girls) - 61 people, the experimental group - young people of both sexes who had mental disorders (schizophrenia, schizoaffective disorder, affective disorders bipolar disorder, personality disorder) – 57. The results indicate the presence of the specific nature of components procrastination and indirect aggression manifestations of different levels at a young age for mental pathology